Gambaran Tingkat Keberhasilan Perawatan Ortodonti di Klinik Ortodonti RSGM-P FK Usakti Berdasarkan Indeks PAR (Laporan Penelitian) - Sintha Paula Madah Pertiwi; Riko Nofrizal (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: The success of orthodontic treatment is very much dependent on the degree of malocclusion of the patient's teeth also affects the success of orthodontic treatment. The success of orthodontic treatment can also be assessed using an index, such as the Peer Assessment Rating Index (PAR).Objective:To describe the success rate of orthodontic treatment in the orthodontic clinic of RSGM-P FKG USAKTI based on the PAR index. Method: Descriptive observational study on a study model of orthodontic clinic patients aged 8-12 years. PAR index was measured in 40 pre emptive study models and orthodontic treatment evaluation study models. The components of the PAR index measured included 5 components, namely the assessment of the maxillary and mandibular anterior segments, the assessment of the right and left buccal segment occlusion scores, the overjet score assessment, the overbite score assessment, and the median line score assessment. Result: There were 47.5% included in the